Brucellosis in Patients with Crimean-Congo Hemorrhagic Fever - Fazilet Duygu (Journal of Arthropod-Borne Diseases, 2017)
Background: Crimean-Congo hemorrhagic fever (CCHF) is a fatal zoonotic viral disease caused by infection with a tick-borne virus of the genus Nairovirus. In this study, we investigated the incidence of brucellosis in patients diagnosed with CCHF. Methods: Overall, 169 patients hospitalized with an initial diagnosis of CCHF were included in 2011 in Tokat/ Turkey. Immunoglobulin M (IgM) antibodies and/or PCR results were used in the laboratory diagnosis of CCHF, while plate and standard tube agglutination (STA) tests were used to diagnose brucellosis. Results: Overall, 120 patients (79%) with positive PCR tests were diagnosed with CCHF. Five (4.16%) were also diagnosed with brucellosis based on the positive plate and STA test results. Four patients (2.36%) had negative CCHF PCR and positive STA test results. Conclusion: Brucellosis and CCHF can mimic each other and that all patients with CCHF or brucellosis should be screened for both conditions.